The Effectiveness of Utilizing the Reading House Media in Fostering Reading Interest among Early Childhood Learners - Supitasari, Evi; Yuniarti, Yuniarti; Zarin, Firdaus (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This study aims to examine the effectiveness of utilizing rumah baca (reading house) media in fostering reading interest among early childhood learners. Designed as an interactive learning tool, the reading house supports both cognitive and affective development through engaging reading activities. The research was conducted at TKIT Al-Karima, located in Kubu Raya, West Kalimantan, using a descriptive quantitative approach with a one-group pretest-posttest design. The sample consisted of 15 children aged 4–5 years from class A2. Data collection involved administering a pretest, implementing the reading house media as the treatment, and conducting a posttest. The results were analyzed using a paired sample t-test via SPSS software. The analysis revealed a t-value of 4.342 at a 0.05 significance level, with the critical t-table value being 1.013. Since the calculated t-value exceeded the critical value (4.342 > 1.013), and the significance (2-tailed) was 0.001 (< 0.05), the findings indicate a statistically significant improvement between pretest and posttest scores. Furthermore, interviews with teachers showed that the use of the reading house media increased children's enthusiasm for reading, boosted their self-confidence, and enhanced their active participation in the learning process. These results suggest that the reading house is an effective medium for improving both reading interest and ability in early childhood education settings.